Interpretation of Specification for Developing Clinical Practice Guidelines of Organic Integration of Traditional Chinese and Western Medicine - JIN Yinghui; YAN Siyu; REN Xiangying; WANG Yongbo; HUANG Qiao; ZHANG Xiaoyu; ZHAO Chen; QIU Ruijin; YOU Liangzhen; SUN Yang; ZHENG Rui; JIANG Yin; et al. (Yixue xinzhi zazhi)
In recent years, the number of clinical practice guidelines for the integration of traditional Chinese medicine (TCM) and western medicine(WM) has been increasing year by year. However, there are obvious problems of "knot without compatibility". The recommendations of TCM and WM are mostly independent, inconsistent with the actual clinical diagnoses and treatment processes, and lacking in important information. All the above issues are unable to bring the role of the cooperation between TCM and WM in improving clinical practice. In order to achieve the organic integration of Chinese and western medicine, the research team has carried out methodological research in response to the above-mentioned problems. In November 2023, China Association for Standardization released the Specifications for Developing Clinical Practice Guidelines for Organic Integration of Traditional Chinese and Western Medicine at the 6th-8th Academic Annual Meeting of the Clinical Research Branch of China Information Association of Traditional Chinese Medicine. Therefore, this paper interprets the formulation process, scope of application and main content of the specification, with the aim of improving the overall quality of related research and promoting the collaborative development of the integration of TCM and WM.